Intercultural Communication: A Study of Normativity and Historicity from a Literature Review Perspective - anshori, Muhammad; Januri, Januri; Alfazri, M.; Ristiyani, Dian Yuly (Program Studi Manajemen Dakwah Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2025)
This study is a comprehensive literature review that examines the dynamics of intercultural communication in Indonesia based on previous studies. The research focuses on two main aspects, namely normativity and historicity. Normativity encompasses the values and social norms that shape patterns of cross-cultural communication, such as customs, speaking etiquette, and social hierarchy. Meanwhile, historicity refers to the historical background that shapes relations between ethnic, religious, and regional groups, including the influence of colonialism, migration, and government policies in shaping Indonesia's multicultural landscape. Data was obtained from 15 primary and secondary sources, including nationally indexed journal articles, academic books, and official reports from international institutions such as UNESCO and the World Bank. The results of the study indicate that intercultural communication in Indonesia is greatly influenced by factors such as language, religious beliefs, social perceptions, and the complex history of interactions between groups. Tensions and harmony in communication often stem from individuals' lack of readiness to understand cultural differences. Therefore, effective communication strategies must include cultural adaptation, strengthening attitudes of tolerance, and improving cultural literacy through education and the media. This study recommends integrating an intercultural approach into education and communication training curricula to build an inclusive and mutually respectful society. These findings provide important contributions to the development of social policies and communication practices amid Indonesia's dynamic cultural diversity.